B Cell-Activating Factor Regulates Different Aspects of B Cell Functionality and Is Produced by a Subset of Splenic B Cells in Teleost Fish - Tafalla, Carolina; González, Lucia; Castro, Rosario; Granja, Aitor G. (Frontiers in Immunology, 2017)
In mammals, B cell functionality is greatly influenced by cytokines released by innate cells, such as macrophages or dendritic cells, upon the early recognition of common pathogen patterns through invariant receptors. B cell activating factor (BAFF) is one of these innate B cell-helper signals and plays a key role in the survival and differentiation of B cells. Although, evolutionarily, teleost fish constitute the first animal group in which adaptive immunity based on Ig receptors is present, fish still rely greatly on innate responses. In this context, we hypothesized that BAFF would play a key role in the control of B cell responses in fish. Supporting this, our results show that teleost BAFF recapitulates mammalian BAFF stimulating actions on B cells, up-regulating the expression of membrane MHC II, improving the survival of fish naïve B cells and antibody secreting cells, and increasing the secretion of IgM. Surprisingly, we also demonstrate that BAFF is not only produced in fish by myeloid cells, but is also produced by a subset of splenic B cells. Thus, if this B cell-produced BAFF proves to be actively regulating this same B cell subset, our findings point to an ancient mechanism to control B cell differentiation and survival in lower vertebrates, which has been silenced in mammals in physiological conditions, but reemerges under pathological conditions, such as B cell lymphomas and autoimmune diseases.